Avaliação da adesão ao tratamento da hipertensão arterial em idosos acompanhados na unidade básica de saúde Dr. Lucas Benjamim na cidade de Mossoró - RN - Taumaturgo, Gabriel Castro (Universidade Federal Rural do Semi-Árido, 2020)
The present study was developed from the perception that it is necessary to measure adherence to the treatment of the most prevalent chronic disease in Brazil, systemic arterial hypertension, which can lead to significant health complications, if not properly treated, in elderly components of the population enrolled by the family health team Dr. Lucas Benjamim, in Mossoró - RN. This research proposes to evaluate adherence to the treatment of arterial hypertension in the elderly enrolled by the family health team of UBS Dr. Lucas Benjamim and it is a cross-sectional study that used a validated questionnaire containing 24 questions about the therapeutic adherence of hypertension . It was shown that 67.5% of the participants are within the appropriate range for therapeutic adherence, 20% are at risk of non-adherence and 12.5% are in a range that indicates inadequate adherence, so that some specific points may be more well worked by professionals. Therefore, we attest to the need for the team to use mechanisms to optimize the profile of compliance with medical guidelines regarding pharmacological and non-pharmacological measures.
Keywords: Adesão terapêutica; Hipertensão arterial; Idosos; Therapeutic adherence; Arterial hypertension; Elderly; CIENCIAS DA SAUDE::MEDICINA